2019
DOI: 10.3390/rs11111304
|View full text |Cite
|
Sign up to set email alerts
|

Passive Microwave Melt Onset Retrieval Based on a Variable Threshold: Assessment in the Canadian Arctic Archipelago

Abstract: The Canadian Arctic Archipelago (CAA) presents unique challenges to the determination of melt onset (MO) using remote sensing data. High spatial resolution data is required to discern melt onset among the islands and narrow waterways of the region. Current passive microwave retrievals use daily averaged 19 GHz and 37 GHz data from the multi-channel microwave radiometer (SMMR) and/or the special sensor microwave/imager (SSM/I). The development of a new passive microwave melt onset method capable of using higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(68 reference statements)
2
7
0
Order By: Relevance
“…While first open water will be later than sea ice melt onset, the weak negative trend in first open water dates (-2.91 d decade -1 , p > 0.05) is consistent with findings from previous studies, highlighting that no significant trends in melt onset dates were found in the CAA (e.g. Mahmud et al 2016;Marshall et al 2019); while other Arctic regions (e.g. Baffin Bay, Eastern Greenland, Barents Sea, Beaufort Sea, and Chukchi Sea) have shown significantly earlier melt onset by 2.3 to 6.9 d decade -1 (e.g.…”
Section: Links In Sea Ice and Snow Phenologysupporting
confidence: 90%
“…While first open water will be later than sea ice melt onset, the weak negative trend in first open water dates (-2.91 d decade -1 , p > 0.05) is consistent with findings from previous studies, highlighting that no significant trends in melt onset dates were found in the CAA (e.g. Mahmud et al 2016;Marshall et al 2019); while other Arctic regions (e.g. Baffin Bay, Eastern Greenland, Barents Sea, Beaufort Sea, and Chukchi Sea) have shown significantly earlier melt onset by 2.3 to 6.9 d decade -1 (e.g.…”
Section: Links In Sea Ice and Snow Phenologysupporting
confidence: 90%
“…Figure 3 shows the time series of the AMSR-E MPF and daily average 2 m air temperature in the ERA5 dataset provided by the European Centre for Medium-Range Weather Forecasts (ECMWF, https://www.ecmwf.int/). The MO date is obtained by using the dynamic threshold variability method based on 36.5 GHz vertically polarized T B data [20]. The FO date is retrieved from the melt/freeze-up algorithm, using 19 and 37 GHz vertically polarized T B data [18].…”
Section: Estimating Meltwater Drainage Onset Timing and Durationmentioning
confidence: 99%
“…These data points outside the possible melt season are problematic and are not to be included; we only used the realistic time series over 10/10 ice concentration and between the MO and FO dates, as the black circles in Figure 3 show. If the threshold of the MO is not determined due to the high inter-quartile range in the histogram of the potential MO [20], a data point of more than 0 • C air temperature is used for determining a realistic time series.…”
Section: Estimating Meltwater Drainage Onset Timing and Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…[11], respectively. In 2012, the MO detections using [9] are not possible since the AMSR2 data are available from 4 July. MO in 2012 is instead detected using the melt/freeze-up algorithm 10].…”
Section: Introductionmentioning
confidence: 99%